Implementation of Grasp (Guide Reading And Summary Procedure) Strategy in Descriptive Text on Students Reading Comprehension - Maizera, Anisa; Roza, Veni; Reflinda, Reflinda; Melani, Melyann (Education Achievement: Journal of Science and Research, 2024)
This research was conducted due to several problems that found by the researcher. This research was aimed to find out the implementation of GRASP (Gude Reading and Summary Procedure) in descriptive text on students reading comprehension at eleventh grade in SMAN 1 Baso. Based on preliminary research, there some problem in teaching reading comprehension that was students were difficult finding main idea, students were bored and lazy to read the text in English, students were difficult understanding the meanings. One of strategy in teaching reading comprehension that can be used is GRASP strategy. Indeed, the researcher wanted to find out how the teacher implemented this strategy in teaching reading. The design of the research was descriptive qualitative research. The data was collected by doing observation using observation checklist, and interview with English teacher at SMAN 1 Baso. The data analyze by using qualitative data analysis by Miles and Huberman. The researcher collected the data, reduced the data, presented the data, and made a conclusion. The researcher found out the teacher implemented the GRASP strategy perfectly and clearly. It is based on the first three classes all of the procedures of GRASP strategy are done perfectly and clearly. Otherwise, in the last class there are three procedures that cannot be done. GRASP strategy can’t be used in all kind of the texts but descriptive text suitable for this strategy. This strategy worth it to use in teaching reading comprehension and based on observation in four classes, the teacher success to implemented the GRASP strategy in the classroom.